Children Have Similar Reverse Transcription Polymerase Chain Reaction Cycle Threshold for Severe Acute Respiratory Syndrome Coronavirus 2 in Comparison With Adults - Polese-Bonatto, Márcia; Sartor, Ivaine Tais Sauthier; Varela, Fernanda Hammes; Giannini, Gabriela Luchiari Tumioto; Azevedo, Thaís Raupp; Kern, Luciane Beatriz; Fernandes, Ingrid Rodrigues; Zavaglia, Gabriela Oliveira; de David, Caroline Nespolo; Santos, Amanda Paz; de Almeida, Walquiria Aparecida Ferreira; Porto, Victor Bertollo Gomes; et al. (The Pediatric infectious disease journal, 2021)
The viral dynamics and the role of children in the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are not completely understood. Our aim was to evaluate reverse transcription polymerase chain reaction (RT-PCR) cycle threshold (Ct) values among children with confirmed SARS-CoV-2 compared with that of adult subjects. Patients (from 2 months to ≤18 years of age and adults) with signs and symptoms of acute SARS-CoV-2 infection for less than 7 days were prospectively enrolled in the study from May to November 2020. All participants performed RT-PCR assay for SARS-CoV-2 detection; Ct values of ORF1ab, N and S gene targets and the average of all the 3 probes were used as surrogates of viral load. There were 21 infants (2 months to <2 years), 40 children (≥2 to <12 years), 22 adolescents (≥12 to <18 years) and 293 adults of 376 participants with confirmed SARS-CoV-2 infections. RT-PCR Ct values from all participants less than 18 years of age, as well as from all childhood subgroups, were not significantly different from adults, comparing ORF1ab, N, S and all the gene targets together (P = 0.453). Ct values for children were comparable with that of adults. Although viral load is not the only determinant of SARS-CoV-2 transmission, children may play a role in the spread of coronavirus disease 2019 in the community.